Increased plasma imatinib exposure and toxicity in chronically treated GIST patients with SARS-CoV-2 infection: a case series - Gagno, Sara; Posocco, Bianca; Orleni, Marco; Cecchin, Eleonora; Fumagalli, Arianna; Guardascione, Michela; Buonadonna, Angela; Polesel, Jerry; Puglisi, Fabio; Toffoli, Giuseppe; Cecchin, Erika (Frontiers in Immunology, 2024)
Introduction Inflammatory factors released during severe coronavirus disease-19 (COVID-19) caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are known to influence drug exposure, but data on the effect of mild infection are few. Here we describe for the first time an increase in plasma imatinib and norimatinib concentrations observed in a series of 5 patients treated with imatinib for gastrointestinal stromal tumor (GIST) after mild COVID-19. Methods The patients were undergoing routine therapeutic drug monitoring (TDM) and pharmacogenetic (PGx) analyses of polymorphisms in genes involved in imatinib metabolism and transport (CYP3A4, CYP3A5, ABCB1, and ABCG2) when SARS-CoV-2 infection occurred. Imatinib and its active metabolite norimatinib concentrations were determined at Ctrough using a validated LC-MS/MS method. PGx analyses were performed by KASP genotyping assays on a Real-Time PCR system. All patients received imatinib 400 mg/day. Case 1 was prospectively monitored. Cases 2-5 were identified retrospectively. Results On average, imatinib Ctrough increased significantly by 70% during COVID-19, whereas norimatinib showed a 44% increase compared with pre-COVID-19 levels. Elevated plasma imatinib concentrations persisted up to 6 months after infection remission. In 3 cases, this increase reflected the occurrence or worsening of imatinib side effects. Conclusion This case-series highlights the clinical impact of SARS-CoV-2 infection on the management of patients with GIST treated with imatinib.